KEMUNCULAN TAGAR #2019GANTIPRESIDEN TERHADAP TINGKAT PARTISIPASI POLITIK DI KALANGAN MAHASISWA PADA PILPRES TAHUN 2019 - Deni Afriyanto; Ubaidullah Ubaidullah; Ardiansyah Ardiansyah (Journal of Political Sphere, 2021)
AbstractThe 2019 election was the battle between the pair of Joko Widodo and Maaruf Amin as candidate number 01 and Prabowo Subianto and Sandiaga Uno as candidate number 02. During the campaign, the hastag #2019GantiPresiden made its public appearance after it was initiated by Mardani Ali Sera. In Banda Aceh, there was an increased percentage of participation of the public to participate in the 2019 election with 72.28 percent of participation compared to that of 2017 with only 64 percent. The increase of participants might have also contributed to the success of candidade number 02 to gain 85.07 percent of votes in Aceh Province compared to candidate 01 who only got 14.92 percent. The aim of this study was to examine the impacts of hastag #2019GantiPresiden in Syiah Kuala Subdistrict of Banda Aceh and to investigate the impacts of the hastag on the presidential election process. This study was based on two theories, i.e. political participation and political communication theories used as instruments to answer the research problems. The method used in this study was mixed methods. The primary data were collected by means of a questionnaire and interview while the secondary data were obtained through literature reviews. The results of this study revealed that there was a correlation between the participation of politics of the youth in the election and the #2019GantiPresiden hastag.